HOSPITAL’S PERFORMANCE MEASUREMENT WITH MALCOLM BALDRIGE METHOD IN EAST JAVA - Made Nita Sintari (Journal of Public Health Research and Community Health Development, 2020)
Background: Malcolm Baldrige method has been widely used to assess institutional performance. However, data obtained from the assessment are still visualized in the form of tables. This kind of visualization for rendering data is less interesting and makes readers difficult to interpret the data. Aims: This study presented some recommendations for data visualization in various forms, such as charts and diagrams to facilitate data interpretation. Methods: This study utilized Microsoft Excel 2007 software to create charts. The data used as an example for analysis was the performance assessment using Malcolm Baldrige method at Muhammadiyah Gresik Hospital in June 2012. Results: The results of this study reported that by using Malcolm Baldrige method, the data could be visualized in forms of bar charts, radar charts, and pie charts. Conclusion: To conclude, performance assessment can be visualized not only in tables but also charts and diagram that have a more visual presentation.Keywords: Charts, performance, Malcolm Baldrige, visualization